The Cult of Poseidon Helikonios - Katsonopoulou, Dora (História: Questões & Debates, 2021)
The cult of Poseidon Helikonios is associated with his primeval aspect of the powerful god of earthquakes and waters. His most antique cult in this capacity, dating from the Mycenaean times, originates from Helike of Achaea on the southwestern shore of the Gulf of Corinth, the place known to Homer as a centre of this worship. The sanctuary of Poseidon Helikonios located in Helike was the holiest for all Ionians; there were also located the ancient ancestral altars for the Ionic race. When the Ionians were expelled from Helike by the Achaeans at the end of the Mycenaean times, they settled in Asia Minor and carried with them the cult of Helikonios. In the paper, the spread of this particular cult from Helike to the Asia Minor coast and farther to the Black Sea region is discussed on the basis of literary, archaeological and numismatic evidence available from the places where the cult held prominent position.